Creativity of Trainee Technology Teachers of the Baltic Countries as Readiness to Educate Learners Meeting the Needs of the Labor Market of the Beginning of the 21st Century - Valantinaitė, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper analyzes the requirements for the labor market at the beginning of the 21st century, and overviews the novelties of employee assessment and selection which make a claim on the school and higher education, in particular teacher training. The priority for a creative society is a creative participant in the labor market. The needs of the multicultural market can be met by people who were brought up in a stable culture and are able to offer uniqueness and novelty, therefore, the paper focuses on the Baltic countries which are similar in their historical, political and geographical situation. The article analyzes the creativity of the trainee Technology teachers in their final years of study in the Baltic countries. Creativity breeds creativity, hence, the creativity of trainee teachers is analyzed as their readiness to educate learners who would meet the requirements of the labor market of the beginning of the 21st century. The activity of a creative person is relevant in diverse contexts from the school to the employer. Technology teachers were selected due to the particularity of their subject. In classes of home economics different school subjects are applied practically, thus the creativity of Technology teachers is becoming exclusive in the context of preparing learners for life. Relating the literature review and the data of a qualitative analysis, it can be anticipated that a creative teacher of Technologies in the Baltic countries can be an indicator of an attractive and successful school of the beginning of the 21st century.